Science on the Summit: Exploring Scientific Tourism Through the Lens of Eighteenth Century Mountain Ascents - Ion Mihailescu; Simon Dumas Primbault; Jérôme Baudry (Revue de Géographie Alpine)
This contribution argues that a particular scientific context made summits a place of interest for eighteenth-century travelers. This development is connected to two particular scientific practices. First, the challenges raised by making the barometer into an instrument capable of measuring the altitude of mountains transformed the summit into a privileged experimental site. Second, the scientific publications which described these experiments acted as guides to the summit for its readers, as shown by the example of the first ascents of Mont Buet by Jean-André Deluc, Marc-Théodore Bourrit, and Horace Bénédict de Saussure. Those who ascended on summits not only followed in the footsteps of Deluc and Saussure, but also imitated some of their scientific practices and observations, though not always with a clear scientific goal of their own. We suggest that these travelers engaged in science not so much because they needed a justification for their ascents, but rather because their experience of the mountain came to be mediated through such instruments, observations and publications. The ambiguity behind these scientific practices lacking a clear scientific purpose draws an interesting parallel between this historical study and the contemporary phenomenon of scientific tourism. Our historical case study indicates how contemporary scientific tourism could rely on a model of public engagement with science informed by the history of science and technology.